2023
DOI: 10.3390/w15152726
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Water Content Based on Hyperspectral Reflectance Combined with Competitive Adaptive Reweighted Sampling and Random Frog Feature Extraction and the Back-Propagation Artificial Neural Network Method

Abstract: The soil water content (SWC) is a critical factor in agricultural production. To achieve real-time and nondestructive monitoring of the SWC, an experiment was conducted to measure the hyperspectral reflectance of soil samples with varying levels of water content. The soil samples were divided into two parts, SWC higher than field capacity (super-θf) and SWC lower than field capacity (sub-θf), and the outliers were detected by Monte Carlo cross-validation (MCCV). The raw spectra were processed using Savitzky–Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…At the same time, the correct model and processing method need to be used, making prediction difficult. For the modeling methods, the overall ranking of model performance is as follows: RF > BPNN > SVM > PLSR, which is consistent with the findings of previous studies, but the order of XGBoost is usually not fixed [37,45,52,53]. The prediction of different soil parameters is different for different data preprocessing methods and modeling approaches.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…At the same time, the correct model and processing method need to be used, making prediction difficult. For the modeling methods, the overall ranking of model performance is as follows: RF > BPNN > SVM > PLSR, which is consistent with the findings of previous studies, but the order of XGBoost is usually not fixed [37,45,52,53]. The prediction of different soil parameters is different for different data preprocessing methods and modeling approaches.…”
Section: Discussionsupporting
confidence: 82%
“…Kawamura et al [35,44] found that the machine learning model showed higher accuracy than the traditional linear model (e.g., multiple linear stepwise regression and partial least squares) when predicting soil parameters (e.g., N and P) using Vis-NIR. Previous research in their study on predicting soil TN using Vis-NIR technology combined with support vector machines, random forests, extreme gradient boosting (XGBoost), and backpropagation neural networks discovered that all machine learning methods could achieve accurate TN predictions, with the model accuracy ranking as follows: RF > BPNN > SVM [37,45,52,53]. XGBoost's performance may be higher or somewhere in between.…”
Section: Introductionmentioning
confidence: 99%
“…Water, an essential element in various forms and compositions, gives rise to intricate mechanisms and pathways that significantly influence the soil environment at multiple levels [2,3]. In the field of agriculture, soil water content (SWC) is vital for plant growth and development [4]. Adequate water supply at different growth stages is essential for any crop, as both too much and too little water can negatively impact crop yield and quality [5].…”
Section: Introductionmentioning
confidence: 99%